Reactions of Carboxylic Acids With an Alcohol Over Acid Materials - Castanheiro, José (2022)
Biodiesel is an alternative to fossil diesel. It is biodegradable and non-toxic. The production of biodiesel is carried out by transesterification and/or esterification reactions. Usually, reactions between a carboxylic acid with an alcohol are carried out using sulfuric and phosphoric acids. Mineral acids (e.g., sulfuric acid) have some problems, such as the separation of reaction mixture. Heterogeneous catalysts can used to replace the homogenous ones. These catalysts have been used for biodiesel production. Recently, acid solids, such as heteropolyacids, activated carbons with sulfonic acid groups, and cation-exchange resins, have been used as catalysts on esterification of free fatty acids (FFAs). This present work is a review about the esterification reactions of carboxylic acid (fatty acid) with an alcohol over solid materials.